Shooting parameters of biathletes in various age groups in 2011-2012 World Championships - Kreivenaite, L. (Education. Physical training. Sport, 2012)
Research background and hypothesis. Physical fitness problems in biathlon are quite extensively discussed, but biathlon shooting in Lithuania is not analyzed enough. The special literature lacks information about the shooting parameters that leaders demonstrate in the world biathlon championships. Moreover, shooting parameters in different age and gender groups have not been analyzed enough. The hypothesis that shooting parameters in adult, youth and junior age group biathletes would differ was tested. Research aim. The aim of our study was to analyze shooting parameters of biathletes in various age groups in 2011-2012 world championships and reveal fundamental differences in the aspects of age and gender. Research methods. Research participants were youths (age: 17-18 years), juniors (age: 19-20 years) and adults (age: 21-41 years), male and female biathletes. The number of subjects was 2175. Descriptive statistical methods were used for data analysis. Research results. Data analysis revealed the main differences in shooting parameters between adult, junior and youth groups, male and female biathletes. Also, comparison of shooting parameters between biathletes in various age groups and leaders in the same group was carried out. Discussion and conclusions. Our research revealed that the highest shooting accuracy was observed in adult male and female biathlete groups (p < 0.025). The shooting accuracy of junior and youth female biathletes was higher than that in the junior and youth male groups (p < 0.05). The longest average shooting time was in youth group (p < 0.001). The shooting time of biathletes in adult group was the shortest. We found that male biathletes in various age groups performed shots in less time compared to female biathletes (p < 0.05). Research results revealed that shooting parameters among leaders statistically significantly differed comparing them with the average shooting parameters in the group (p < 0.05).